Active and Passive Coastal Pavement Degradation - Hyatt, James Andrew (My University, 1985)
Inland degradational trends of coastal dolomite pavements (on the Amabel formation near Tobermory Ontario Map 1) were examined in three wave energy settings: passive, intermediate, and active shores.
Six pavement property trends were examined to determine the effect of low fetch lengths (7-10 km - Ford 83) and long shallow wave approach (Map 1) on the break-up of passive coastal pavements (south-west Bear's Rump Island): vegetation cover , grike dimensions, fracturing, pitting, shattering and flaking, and soil and rubble depths.
Detailed analysis of small scale surface solution features, "karren", was undertaken at five 1 m sample grids on the intermediate average fetch 70-90 km -Grosset 85) Cyprus Lake provincial park pavements.
Keywords: degradational, costal dolomite pavements, shores, passive, active, intermediate, vegetation cover, grike, fracturing, pitting, shattering, flaking, soil, rubble depths, surface morphology, exposure age, vegetation cover